2022
DOI: 10.1177/23337214221097750
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, General Self-Efficacy, Fear of Falling, and Physical Activity Among Older Adults in a Middle-Income Country

Abstract: Objectives: To investigate the levels and interrelationships between fear of falling (FOF), physical activity (PA), social support (SS), and general self-efficacy (GSE) among older adults in a Nigerian community. Methods: This was a cross-sectional survey involving 100 older adults (65.0% females; mean age = 74.25 ± 8.01 years) consecutively recruited from Nnewi community. Participants’ FOF, PA, GSE, and SS were assessed using standardized questionnaires. Data were analyzed using descriptive statistics, Spearm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Numerous studies have examined the association between general SOSU and PA in older adults, but the methods used to measure SOSU vary. Some studies have used instruments such as the DSSI [ 33 , 38 , 39 ], the MSPSS [ 36 , 40 , 41 ] or the LSNS [ 23 , 42 , 43 ], while most measure general SOSU with very few items, both of which make it difficult to compare results. Nonetheless, despite these measurement differences, the majority of studies consistently show a significant positive relationship between general SOSU and PA in older adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have examined the association between general SOSU and PA in older adults, but the methods used to measure SOSU vary. Some studies have used instruments such as the DSSI [ 33 , 38 , 39 ], the MSPSS [ 36 , 40 , 41 ] or the LSNS [ 23 , 42 , 43 ], while most measure general SOSU with very few items, both of which make it difficult to compare results. Nonetheless, despite these measurement differences, the majority of studies consistently show a significant positive relationship between general SOSU and PA in older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Oktaviana et al conducted a longitudinal study in Indonesia measuring SOSU provision from living with a spouse and children and found no significant association between SOSU and PA [ 126 ]. Okoye et al found a negative association between perceived SOSU and PA in older Nigerians [ 36 ]. Several studies have focused on the sources of SOSU but found inconclusive evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of significant difference in social support from friends between the two groups could stem from the fact that participants in the ALFs usually cultivate new friendship with their caregivers and fellow residents ( Ziemba et al, 2008 ) who provide them with the required social support thereby masking the loss of support from their former friends. A recent local study had also reported a high level of social support among community-dwelling older adults ( Okoye et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Social support associated with medication adherence and the identification of barriers to adherence requires an understanding of factors related to the patient's understanding, beliefs or abilities; socioeconomic factors; factors related to the health condition of the elderly, such as the presence of comorbidities; factors related to therapy, such as the complexity of the medication regimen; and factors related to the health system or health team, such as communication with health professionals. [11][12][13][14][15] Social support is characterized by the perception or lived experience of the care, recognition and stigma that other people have of this support, which can be identified as something that refers to the resources made available in situations of need by other people or institutions. The assessment of social support measures the degree to which interpersonal relationships represent certain functions and provide support for the elderly in times of crisis or readaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of social support measures the degree to which interpersonal relationships represent certain functions and provide support for the elderly in times of crisis or readaptation. [11][12][13][14][15] Social support usually has four dimensions: instrumental support, identified as the provision of tangible help and services; informational support, demonstrated by providing useful information, advice or suggestions to solve problems; evaluative support, inferred by the delivery of information to the other that is useful for self-assessment; and emotional support, which involves the expression of empathy, love, trust and concern. [11][12][13][14][15] With regard to social support, as one of its critical functions of social relationships, it has health benefits at different levels of care, being offered by an institution or person, and when perceived by the recipient in a positive way, it has been considered a protective factor to assist in the treatment of diseases and has a favorable relationship with health effects, that is, it is not enough to offer support to a person, but it must also be experienced as important and necessary by the recipient so that it can be related to positive effects.…”
Section: Introductionmentioning
confidence: 99%